PENGARUH KEPEMIMPINAN DAN PERPUTARAN KARYAWAN SERTA PERILAKU TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK SUMSEL BABEL PALEMBANG - Santi Puspita (Universitas PGRI Palembang, 2014)
Influence of leadership and rotation of employee and also behavior to working satisfaction of employees at PT. Bank Sumsel Babel Palembang. This research aims to know the influence of leadership of employees at PT. Bank Sumsel Babel Palembang either in collective or partial by using a research design of cluster sampling technique, that is employees of Bank Sumsel Babel amount a slovin formula to be obtained 76 people. The data is collected through questionnaire answer of responders about research variable with likert scale quality from 1 up to 5. The data analysis is conducted descriptively after converting it to interval form by using succesive interval method. The analysis of multiple linear regression is conducted by using an aid of SPSS Program for windows version 16 to test a research hypothesis. The result of t test analysis indicate that variable of leadership, rotation of employees, behavior a real influence to the working satisfaction of employees of Bank Sumsel Babel Palembang with constant amount to 0,866. The leadership variable has a real influence with regression coeficient amount to 0,40. The variable of employees rotation has regression coeffisient amount to 0,163 and behavior of employees has regression coefficient amount to 0,234. The analysis result of F test variable is a F count amount 45, 689 in the fact is bigger than F table 0,05 = 2,732. It means that research with error level 0,05, leadership, rotation of employees and behavior in collective have influence to the working satisfaction of employees at Bank Sumsel Babel Palembang.